The Group A Streptococcus serotype M2 pilus plays a role in host cell adhesion and immune evasion. Issue 2 (14th November 2016) - Tsai, Jia‐Yun C.; Loh, Jacelyn M. S.; Clow, Fiona; Lorenz, Natalie; Proft, Thomas
Summary: Group A Streptococcus (GAS), or Streptococcus pyogenes, is a human pathogen that causes diseases ranging from skin and soft tissue infections to severe invasive diseases, such as toxic shock syndrome. Each GAS strain carries a particular pilus type encoded in the variablef ibronectin‐binding, c ollagen‐binding, T antigen (FCT) genomic region. Here, we describe the functional analysis of the serotype M2 pilus encoded in the FCT‐6 region. We found that, in contrast to other investigated GAS pili, the ancillary pilin 1 lacks adhesive properties. Instead, the backbone pilin is important for host cell adhesion and binds several host factors, including fibronectin and fibrinogen. Using a panel of recombinant pilus proteins, GAS gene deletion mutants and Lactococcus lactis gain‐of‐function mutants we show that, unlike other GAS pili, the FCT‐6 pilus also contributes to immune evasion. This was demonstrated by a delay in blood clotting, increased intracellular survival of the bacteria in macrophages, higher bacterial survival rates in human whole blood and greater virulence in a Galleria mellonella infection model in the presence of fully assembled FCT‐6 pili. Abstract : The Group A Streptococcus serotype M2 strain carries a pilus encoded in the FCT‐6 region. This pilus type has never been characterised before. We found that in addition to its function as an adhesive structure, the FCT‐6 pilus also plays a role in immune evasion. This appears to be mediated mainly by the backbone pilin which was shown to bind fibrinogen.